Evaluation of crop management options for replanting of coconut plantations devastated by lethal yellowing disease in Ghana - E. Andoh-Mensah; X. Bonneau; J. Ollivier; B. N. Nuertey; S. K. Dery (International Coconut Community Journal, 2005)
Evaluation of four coconut management options was carried out from May 1999 to May 2004 in the coconut belt of the Western and Central Regions of Ghana for replanting of coconut plantations devastated by the Cape St Paul Wilt Disease of Ghana. Coconut hybrid identified for the replanting was MYD x VTT. On fertile soils just intercropping of inter-rows with food crops proved appropriate for managing the coconut hybrid successfully. On low fertile soils however, fertilization was required in addition to intercropping for proper management of the hybrid. Where intercrops were fertilized the coconut palms benefited from the residual effect. While Pueraria phaseoloides did not have any visible impact, Cassia siamea was antagonistic to growth and development of the young coconut hybrid. Fertilized intercropping was more profitable especially on low fertile soils.